Age Estimation Using the Radiographic Visibility of the Periodontal Ligament in Mandibular Third Molars in Mysore Population- A Retrospective Study - Karthikeya Patil; Mahima VG; Poornima Chandran; Bharathi Penumatsa; Nagabhushana Doggalli; Sanjay CJ (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: This study was conducted to assess the reliability of age estimation using the radiographic visibility of periodontal ligament surrounding the roots of completely erupted mandibular 3rd molar.Materials and methods:Visibility ofperiodontal ligament was assessed in completely erupted mandibular third molars, in a sample of 135 panoramic radiographs, of which 55 belonging to females and 80 to males, from a Mysore population aged 18to 32 years. A classification of four stages based on the visual phenomenon of disappearance of the periodontal ligament of fully mineralized third molars was used. For each stage, mean, standard deviation, minimal & maximal age were assessed.Results:The relationship between age and stage of periodontal ligament had a statistical significance for both sexes.In this population, stage 1 can be used for predictability of age above 19 years and stage 3 for predictability of age above 23 years. No significant correlation exists between periodontal ligament visibility and gender of the individual.Conclusion:Thistechnique is advocated for determining age above 19 years as it is a relatively simple and reliable method. Differences exist in different ethnicities demanding specific population standards.